Anterior eye surface changes following miniscleral contact lens wear. Issue 1 (February 2019) - Consejo, Alejandra; Behaegel, Joséphine; Van Hoey, Maarten; Wolffsohn, James S.; Rozema, Jos J.; Iskander, D. Robert
Highlights: Short-term miniscleral contact lens wear significantly alters limbal radius and scleral elevation. No corneal flattening was found as a consequence of short-term miniscleral contact lens wear. Scleral flattening was not fully reversed 3 h after lens removal in majority of cases. These highlights correspond to healthy eyes. Abstract: Purpose: To quantify the effect of short-term miniscleral contact lens wear on the anterior eye surface of healthy eyes, including cornea, corneo-scleral junction and sclero-conjuctival area. Methods: Twelve healthy subjects (29.9 ± 5.7 years) wore a highly gas-permeable miniscleral contact lens of 16.5 mm diameter during a 5-hour period. Corneo-scleral height profilometry was captured before, immediately following lens removal and 3 h after lens removal. Topography based corneo-scleral limbal radius estimates were derived from height measurements. In addition, elevation differences in corneal and scleral region were calculated with custom-written software. Sclero-conjuctival flattening within different sectors was analysed. Results: Short-term miniscleral lens wear significantly modifies the anterior eye surface. Significant limbal radius increment (mean ± standard deviation) of 146 ± 80 μm, (p  =  0.004) and flattening of −122 ± 90 μm in the sclero-conjuctival area, ( p  << 0.001) were observed immediately following lens removal. These changes did not recede to baseline levels 3 h after lens removal. The greatest anterior eye surface flattening was observed in the superior sector. No statistically significant corneal shape change was observed immediately following lens removal or during the recovery period. Conclusions: Short-term miniscleral contact lens wear in healthy eyes does not produce significant corneal shape changes measured with profilometry but alters sclero-conjuctival topography. In addition, sclero-conjuctival flattening was not uniformly distributed across the anterior eye.